The beginner's guide to wheel throwing : a complete course for the potter's wheel - Weber, Julia (Julia Claire) (Essential ceramics skills., 2021)
The Beginner's Guide to Wheel Throwing is a friendly, contemporary take on the classic wheel-throwing book--perfect for new and returning ceramic artists.